‘Surviving’ at the margins: the impact of COVID-19 on vulnerable groups in South Africa. - Malebane, Matlhogonolo Keoreeditse (Stellenbosch : Stellenbosch University, 2025)
Thesis (MPhil)--Stellenbosch University, 2024.